2018
DOI: 10.1007/s13197-018-3460-z
|View full text |Cite
|
Sign up to set email alerts
|

The compositional, physicochemical and functional properties of germinated mung bean flour and its addition on quality of wheat flour noodle

Abstract: Despite sprouted grains have high nutritional and functional properties, their exploration in mung bean and application in traditional foods are limited. The effects of germination of mung bean for 12, 24, 36, 48, 60 and 72 h on compositional, physicochemical and functional properties of its flour were investigated. The effects of incorporation of germinated mung bean flour at different levels (0, 10, 20 and 30%) on noodles making properties of wheat flour were evaluated 0. The protein content increased while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 28 publications
4
42
0
1
Order By: Relevance
“…A replacement of legume protein with gluten, and hence deterioration of protein network might have caused such an increase in cooking loss (Torres et al, 2007). In addition, germination process itself enhances soluble protein and simple carbohydrates of mung bean, which in turn dissolve into water while cooking and hence lead to an increase in the cooking loss (Liu et al, 2018). Our results agree with those reported by Bilgiçli and İbanoğlu (2015).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…A replacement of legume protein with gluten, and hence deterioration of protein network might have caused such an increase in cooking loss (Torres et al, 2007). In addition, germination process itself enhances soluble protein and simple carbohydrates of mung bean, which in turn dissolve into water while cooking and hence lead to an increase in the cooking loss (Liu et al, 2018). Our results agree with those reported by Bilgiçli and İbanoğlu (2015).…”
Section: Resultssupporting
confidence: 89%
“…In addition, Sissons et al (2010) revealed positive impacts on dough strength, firmness and stickiness of fiber-enriched spaghetti with addition of 0.5% of TGase. To the best of our knowledge, three studies (Slathia et al, 2016;Slathia et al, 2018;Liu et al, 2018) used germinated mung bean flour (GMF) in noodle formulation so far. This is one of the first reports to show the effect of TGase on the physical and sensory properties and cooking quality of germinated (96 h) mung bean noodles.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in hardness and chewiness of noodles contributed to alter the textural properties and strength of the noodles, indicating that <6% HEP could improve the edible quality of noodles due to the increased soluble and insoluble dietary fiber. However, adding too much HEP affected the textural properties of the noodles, which was associated with the dilution of the gluten content (Liu et al., 2018). HEP partially replaced wheat flour to reduce the content of gluten in noodles; besides, denaturation and gelation of proteins during cooking could lead to a further reduction in gluten of cooked noodles (Shiau, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…The addition of modified and unmodified starch had no positive effect on the springiness of the noodles and even reduced the springiness of the noodles, such as the springiness of Native flour, NTS‐F, PAS‐F, and CBS‐F was 0.092, 0.857, 0.871, and 0.885. This was because the protein content was negatively correlated with the springiness of the noodles, and adding starch reduced protein content and led to reducing noodles’ springiness (Liu et al, ).…”
Section: Resultsmentioning
confidence: 99%